Percepción de la calidad de servicio por los clientes externos de la cooperativa de ahorro y crédito UNIBLOCK y SERVICIOS LTDA. de la ciudad de Latacunga. - Molina Maigua, Nelly Marisol (2020)
In the present research work, different conceptualizations that define the quality of service in a financial institution were reviewed, having as objective to evaluate the perception of the quality of service by the external clients Cooperativa de Ahorro y Crédito “UNIBLOCK” y Servicios Ltda. of the city of Latacunga, for the effect a quantitative methodology was applied, with a descriptive approach of non-experimental design and of cross section, the instrument validated was the model SERVPERF by Cronin and Taylor (1992, 1994); the used technique is a questionnaire that consists of 22 questions in a scale of Likert of 7 points structured by five dimensions: tangible aspects, reliability, capacity of answer, security and empathy, designed to measure the quality of the service perceived by the users, on the basis of the mentioned it was demonstrated that a 8752% of the population, corresponding to the empathy variable, are in total agreement with the attention and service received. As for the direct beneficiaries, we have the executives that make up this institution who will have the results that will allow them to make decisions to improve if necessary, and also to achieve a higher level of segmentation within the market and as indirect beneficiaries to external customers, since through the improvement actions a more optimal service with a highly acceptable quality will be determined. The research was feasible thanks to Cooperativa de Ahorro y Crédito; in the same way the students applied the theoretical knowledge about customer service and the necessary resources for its development. The theme executed is of great interest to the credit unions since they will be able to employ strategies with the purpose of building customer loyalty and strengthening themselves in the financial market.